The Geographies of Policy Translation: How Nudge Became the Default Policy Option. (February 2014) - Jones, Rhys; Pykett, Jessica; Whitehead, Mark
This paper examines the emergence of libertarian paternalism or 'nudge' as a rationale of government in the UK and charts the way in which this development has been enabled by, and has enabled, a process of policy translation. We examine: the reasons for the emergence of libertarian paternalism in the UK; the processes that have enabled libertarian paternalism to become a significant way of framing policy in the UK for both the New Labour and the Coalition administrations; the way in which this set of policy initiatives has been predicated upon a process of social and spatial embedding that has seen it become interpreted as a meaningful and default solution to a whole host of social ills. We conclude by arguing that there is a need to appreciate both the political malleability of libertarian paternalism as a concept and the complex geographies that have enabled it to assume political significance in the UK.